Dynamics of the Standard Model Second edition - Donoghue, John F. (Cambridge University Press, 2014)
Describing the fundamental theory of particle physics and its applications, this book provides a detailed account of the Standard Model, focusing on techniques that can produce information about real observed phenomena. It begins with a pedagogic account of the Standard Model, introducing essential techniques such as effective field theory and path integral methods. It then focuses on the use of the Standard Model in the calculation of physical properties of particles. Rigorous methods are emphasized, but other useful models are also described. The second edition has been updated to include theoretical and experimental advances, such as the discovery of the Higgs boson, our understanding of neutrinos, and the major advances in CP violation and electroweak physics. This book is valuable to graduate students and researchers in particle physics, nuclear physics and related fields. This edition, first published in 2014, has been reissued as an Open Access publication.